(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2020)
Piroxicam (PRX) was determined in pharmaceutical capsules with differential pulse voltammetry (DPV) in a three electrode system consisting of a pencil graphite electrode (PGE) as working electrode, a Pt wire and a reference electrode of Ag/AgCl/KCl 3 M. An irreversible oxidation peak was observed in Epa c.a. 0.6 V, which correlates to the oxidation of PRX. The coefficient of linear correlation obtained was 0.9946, with limit of detection of 2.1 µM and limit of quantification of 4.7 µM. PGE assays showed good analytical performance compared to high performance liquid chromatography and spectrophotometry, showing the potential to be further developed and employed in quick and simple analyses.